2013
DOI: 10.1371/journal.pone.0068269
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-HisCl1 Receptor Axis Regulates Wake-Promoting Signals in Drosophila melanogaster

Abstract: Histamine and its two receptors, histamine-gated chloride channel subunit 1 (HisCl1) and ora transientless (Ort), are known to control photoreception and temperature sensing in Drosophila. However, histamine signaling in the context of neural circuitry for sleep-wake behaviors has not yet been examined in detail. Here, we obtained mutant flies with compromised or enhanced histamine signaling and tested their baseline sleep. Hypomorphic mutations in histidine decarboxylase (HDC), an enzyme catalyzing the conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…The different physiological defects shown by ebony 1 and tan 1 demonstrate that NBAD metabolism is more important than previously known for the homeostasis and the normal function of the nervous system. Moreover, NBAD-synthase can metabolize other biogenic amines such as octopamine, tyramine, histamine and 5-HT, which are also involved in the regulation of locomotor activity and sleep in flies (Yuan et al, 2006;Crocker & Sehgal, 2008;Chen et al, 2013;Oh et al, 2013). The NBAD-hydrolase enzyme is also able to hydrolyze other β-alanyl derivatives (True et al, 2005;Pérez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The different physiological defects shown by ebony 1 and tan 1 demonstrate that NBAD metabolism is more important than previously known for the homeostasis and the normal function of the nervous system. Moreover, NBAD-synthase can metabolize other biogenic amines such as octopamine, tyramine, histamine and 5-HT, which are also involved in the regulation of locomotor activity and sleep in flies (Yuan et al, 2006;Crocker & Sehgal, 2008;Chen et al, 2013;Oh et al, 2013). The NBAD-hydrolase enzyme is also able to hydrolyze other β-alanyl derivatives (True et al, 2005;Pérez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in both mammals and insects, dopaminergic (mammals: [8 •• ,9 •• ]; insects: [10,11]), noradrenergic (mammals: [12]; insects: [13]), and histaminergic (mammals: [14]; insects: [15]) transmissions promote wakefulness, while GABAergic (mammals: [4 • ]; insects: [16,17]) and serotonergic (mammals: [18]; insects: [19]) transmissions promote sleep. This conservation suggests an ancient and common origin for sleep [6].…”
Section: Neuronal Circuitry Of Sleep/wake State Regulationmentioning
confidence: 99%
“…Together, this suggests that the effect of histidine on the growth of nerfin-1 clones is mediated by downstream metabolites 3-methyl-L-histidine and histamine. However, when we knocked down CG3454, encoding a predicted histidine decarboxylase (HDC, RNAi knockdown efficiency previously quantified in Oh et al, 2013) catalysing the conversion of L-histidine into histamine (Hong et al, 2006), we observed a 50% decrease in nerfin-1 but not wildtype clonal volume (Figs 2E and EV3C), which can be partially rescued by supplementation with dietary histamine (Fig EV3D). Together, these results suggest that histamine signalling via its receptor is not required for nerfin-1 clonal growth.…”
Section: Of 12mentioning
confidence: 83%
“…Together, these results suggest that histamine signalling via its receptor is not required for nerfin-1 clonal growth. However, when we knocked down CG3454, encoding a predicted histidine decarboxylase (HDC, RNAi knockdown efficiency previously quantified in Oh et al, 2013) catalysing the conversion of L-histidine into histamine (Hong et al, 2006), we observed a 50% decrease in nerfin-1 but not wildtype clonal volume (Figs 2E and EV3C), which can be partially rescued by supplementation with dietary histamine (Fig EV3D). Hdc knockdown in nerfin-1 clones decreased clonal volume concomitant with an inhibition of neuron-to-neuroblast reversion, reflected by a drop in the proportion of Deadpan (Dpn + ) NBs and an increase in the proportion of embryonic lethal abnormal vision (Elav + ) neurons per clone ( Fig 2F and G), without significantly impacting on cell death or cell mitoses (Fig EV3E and F).…”
mentioning
confidence: 83%
See 1 more Smart Citation